2017
DOI: 10.1111/tbed.12693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bovine viral diarrhoea virus control strategies in dairy herds in Hokkaido, Japan, using stochastic modelling

Abstract: SummaryBovine viral diarrhoea virus (BVDV) infection in cattle can result in growth retardation, reduced milk production, reproductive disorders and death. Persistently infected animals are the primary source of infection. In Hokkaido, Japan, all cattle entering shared pastures in summer are vaccinated before movement for disease control. Additionally, these cattle may be tested for BVDV and culled if positive.However, the effectiveness of this control strategy aiming to reduce the number of BVDV-infected anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This is most likely due to the paucity of BVDV seroconversion data, especially in extensively grazed beef herds. Other studies have used a commonly reported value from intensively managed dairy herds to explain BVDV spread [9, 1316]. However, more efforts should be made to estimate robust values based on empirical data that take into consideration other herd-level management factors that can affect BVDV transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most likely due to the paucity of BVDV seroconversion data, especially in extensively grazed beef herds. Other studies have used a commonly reported value from intensively managed dairy herds to explain BVDV spread [9, 1316]. However, more efforts should be made to estimate robust values based on empirical data that take into consideration other herd-level management factors that can affect BVDV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most commonly used within-herd BVDV transmission rates for PI animals was suggested by Viet et al [7], who set the value to 0.5 per PI animal per day (using frequency-dependent assumption) based on other reports [11, 12]. Although it was not estimated from empirical data, the suggested value successfully explained the BVDV spread on a dairy farm, and their method has been reproduced and adopted by subsequent modellers who simulated BVDV spread under their own epidemiological circumstances [9, 1316]. However, as briefly pointed out in the original paper, a robust transmission rate should be estimated based on longitudinal observations of individual BVDV infection status while considering other management factors, such as production type, population size or density, or herd structure, since those factors can affect BVDV transmission rates within individual herds [14, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Animal movement is commonly recognized as one of the risk factors of spreading BVD infection [ 16 ], while the relationship between animal movement and BVD infection has seldom been reported in Japan [ 17 ]. Given the transmission mode of BVDV, the presence of infected and sensitive individuals together in a certain space should be essential to establish disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models dealing with BVD have been developed to enable us to simulate its spread in the area specified in the computer program and to identify factors affecting intra- or inter-herd disease spread [8, 10, 12, 17, 18, 39]. Indeed, simulation analyses of various control measures for BVD in Japan using a stochastic model or a scenario tree were recently reported [19, 35]; however, the cost effectiveness of the BVD control measures was not fully analyzed.…”
mentioning
confidence: 99%